1994
DOI: 10.1088/0953-8984/6/10/014
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of the photodissociation of physisorbed O2/graphite

Abstract: We have investigated the vacuum ultra-violet photodissociation of molecular O2 physisorbed on graphite using synchrotron radiation with photon energies in the range 13-35 eV. The yield of desorbed O+ ions shows a threshold at approximately 19.5 eV and resonances at 24.5 eV and 28.5 eV, contrasting strongly with the gas phase photodissociation cross section. The principal mechanism of O+ production appears to be dipolar dissociation driven by photoelectrons generated in the substrate. An enhancement in the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…However, relatively little work has been undertaken to study photon-stimulated desorption of negative ions. [1][2][3][4][5] Several photodissociation/photodesorption mechanisms have been proposed. [6][7][8][9][10][11][12][13] For the desorption of negative ions, the incident photon may excite the adsorbed molecule AB to a neutral Rydberg state.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, relatively little work has been undertaken to study photon-stimulated desorption of negative ions. [1][2][3][4][5] Several photodissociation/photodesorption mechanisms have been proposed. [6][7][8][9][10][11][12][13] For the desorption of negative ions, the incident photon may excite the adsorbed molecule AB to a neutral Rydberg state.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of gas-phase CF 3 Cl, Jochims et al 26 have measured the photoabsorption spectrum, and observed various absorption maxima in the photon energy range 9-25 eV. In an electron energy loss spectroscopy ͑EELS͒ experiment of gas-phase CF 3 Cl, King et al 27 have classified the Rydberg states involved in the transitions for the features in the EELS spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations